Common Bacterial Causes of Urethritis in Men: Diagnosis and Treatment - Jahan, Ferdush; Shamsuzzaman, SM; Akter, Sonia; Bhuya, Shahed Kamal (Bangladesh Journal of Medical Microbiology, 2019)
Abstract not available Bangladesh J Med Microbiol 2019; 13 (1): 24-29